The Effect of Think-Pair-Share on Eleventh Grade Students’ Speaking Performance: A Quasi-Experimental Study - Fatur Rahman; Abdul Kamaruddin; Zarkiani Hasyim (Journal of General Education and Humanities, 2026)
Students in EFL classrooms often exhibit low participation in speaking activities, leading to passive interaction and limited oral practice. Therefore, this study aimed to examine the effect of applying the Think-Pair-Share (TPS) technique on improving students’ speaking skills at SMAN 5 Palu. A quasi-experimental design with pre-test and post-test was employed involving two intact classes selected through purposive sampling: class XI M9 as the experimental group and class XI M7 as the control group, each consisting of 35 students. The experimental group received instruction using the TPS technique, while the control group received conventional instruction. Students’ speaking performance was assessed based on accuracy, fluency, and comprehensibility. Data from pre- and post-tests were analyzed using an independent-samples t-test. The results showed a statistically significant improvement in students’ speaking skills after the implementation of the TPS technique. The experimental mean score increased from 30.20 on the pre-test to 67.14 on the post-test, whereas the control group showed only a slight increase from 30.40 to 41.45. The statistical analysis indicated a significant difference between the two groups, t (68) = 12.20, p < .05. These findings indicate that the Think-Pair-Share technique is effective in enhancing students’ speaking performance.